Research in Educational Technology: Framing MEG’s Work - Czerniewicz, Laura (Proceedings of the International Conference on Networked Learning, 2002)
What frames MEG research? This paper explores the way we mediate a range of interests, negotiate a number of possibilities and make hard choices in a tricky environment.I will reflect on issues, tensions and actors which arise from the politics of our context, and comment on how we in MEG have responded to them, engaged with them and attempted to influence them.